Prevalence of underweight, stunting and wasting in under five years old children based in the WHO-2006 and CDC-2000 growth standard on Kintamani, Bangli - I Gusti Lanang Sidiartha (Indonesian Pediatric Society, 2008)
Background Healthy children will have normal growth according totheir age and gender. To assess and monitor the growth of children, agrowth standard is needed. The WHO and CDC released a newgrowth standard to replace the 1977 NCHS growth standard in April2006 and May 2000 respectively.Objective To obtain the prevalence of underweight, stunting andwasting in less than five years old children based on the WHO-2006and CDC-2000 growth standard and compared the results.Methods A cross-sectional study was conducted in Songan Village,District of Kintamani, Bangli on December 2006. Healthy childrenaged 0-59 months who visited the study site were enrolled.Anthropometric data including weight and length/height were obtainedusing standard anthropometrics procedures by trained doctor assistants.Nutritional status was determined by calculating Z-score values (cut-off point -2SD) weight-for-age (underweight), length/height-for-age(stunting) and weight-for-length/height (wasting) using WHO-2006and CDC-2000 growth standard. McNemar test was done to compareboth results and P<0.05 was considered as a statistically significant.Results There were 264 children, consisted of 139 (52.7%) male and125 (47.3%) female. The prevalence of underweight, stunting andwasting based on WHO 2006 was 20.5%, 20.1% and 45.1%respectively and based on CDC 2000 was 26.5%, 12.1% and 52.3%.The difference was statistically significant (P<0.0001).Conclusion The prevalence of underweight and wasting in childrenless than five years old based on the WHO-2006 was lower comparedto that based on CDC-2000, while the prevalence of stunting washigher.